Placenta Peptide Can Protect Mitochondrial Dysfunction through Inhibiting ROS and TNF-α Generation, by Maintaining Mitochondrial Dynamic Network and by Increasing IL-6 Level during Chronic Fatigue - Muluye, Rekik A.; Bian, Yuhong; Wang, Li; Alemu, Paulos N.; Cui, Huantian; Peng, Xiaofei; Li, Shanshan (Frontiers in Pharmacology, 2016)
Background: Level of fatigue is related to the metabolic energy available to tissues and cells, mainly through mitochondrial respiration, as well fatigue is the most common symptom of poorly functioning mitochondria. Hence, dysfunction of these organelles may be the cause of the fatigue seen in CF. Placenta has been used for treatment of fatigue and various disease, moreover peptides has known protect mitochondrial viability, and alleviate fatigue. These properties of placenta and peptides may link with its effect on mitochondria; therefore, it is highly important to investigate the effectiveness of placenta peptide on fatigue and mitochondrial dysfunction. Methods: - After administration of sheep placenta peptide (SPP) for one month, mice’s were forced to swim till exhaustion for 90 minute to induce chronic fatigue. Electron microscopic examination of skeletal muscle mitochondrial structure, tissue MDA, mitochondrial SOD and serum inflammatory cytokines level were investigated in order to determine the potential effect of sheep placenta peptide (SPP) on mitochondria during CF. Rat skeletal muscle (L6 cell) were also treated with different concentration of SPP to determine the effect of SPP on cell viability using MTT assay. Results: - Our finding revealed that forced swimming induced fatigue model can cause mitochondrial damage through ROS mediated lipid peroxidation and TNF-α elevation. Whereas SPP protected fatigue induced mitochondrial dysfunction through preventing ROS and TNF-α generation, by maintaining mitochondrial dynamic network and by increasing serum IL-6 level. Conclusion: - SPP can protect damage in mitochondrial components which will allow proper functioning of mitochondria that will in turn inhibit progression of chronic fatigue. Therefore, SPP may represent a novel therapeutic advantage for preventing mitochondrial dysfunction in patients with chronic fatigue.